Hubungan Perilaku dan Pengawasan Terhadap Penerapan 5S Pada Pekerja di Departemen Jetty PT. XYZ - Rafli Rizkina Arifin; Yanuar Pandu Negoro; Hidayat Hidayat (Fakultas Teknik, 2023)
Companies must not only offer appropriate infrastructure in their production processes to attain optimum profitability, but they must also cultivate a healthy corporate culture. Univariate analysis is used to describe the properties of each variable's frequency distribution in the table. Bivariate analysis, on the other hand, is used to assess the association between two variables, with the chi-square test used to determine the link. Several adjustments are proposed to boost the efficacy of using the 5S Method. These enhancements may be made by conducting bivariate and univariate analyses to discover variables that impact the performance of the 5S Method implementation. This allows proposals for improvement to be developed and executed. To define the measuring scale, researchers utilized a Likert scale to disseminate the questionnaire. The signature value of 0.044 is less than the 0.05 significance threshold, hence the null hypothesis (H0) is accepted and the alternative hypothesis (Ha) is rejected. As a result, it is possible to infer that there is a considerable link between work supervision and 5S implementation in the PT XYZ Jetty department. According to the research results, there is a link between the conduct of XYZ workers and the monitoring of the 5S implementation process.